The AZFc region of the Y chromosome: at the crossroads between genetic diversity and male infertility - Navarro-Costa, Paulo (2011)
BACKGROUND: The three azoospermia factor (AZF) regions of the Y chromosome represent genomic niches for spermatogenesis genes. Yet, the most distal region, AZFc, is a major generator of large-scale variation in the human genome. Determining to what extent this variability affects spermatogenesis is a highly contentious topic in human reproduction. METHODS: In this review, an extensive characterization of the molecular mechanisms responsible for AZFc genotypical variation is undertaken. Such data are complemented with the assessment of the clinical consequences for male fertility imputable to the different AZFc variants. For this, a critical re-evaluation of 23 association studies was performed in order to extract unifying conclusions by curtailing methodological heterogeneities. RESULTS: Intrachromosomal homologous recombination mechanisms, either crossover or non-crossover based, are the main drivers for AZFc genetic diversity. In particular, rearrangements affecting gene dosage are the most likely to introduce phenotypical disruptions in the spermatogenic profile. In the specific cases of partial AZFc deletions, both the actual existence and the severity of the spermatogenic defect are dependent on the evolutionary background of the Y chromosome. CONCLUSIONS: AZFc is one of the most genetically dynamic regions in the human genome. This property may serve as counter against the genetic degeneracy associated with the lack of a meiotic partner. However, such strategy comes at a price: some rearrangements represent a risk factor or a de-facto causative agent of spermatogenic disruption. Interestingly, this precarious balance is modulated, among other yet unknown factors, by the evolutionary history of the Y chromosome.